Ginsenoside Rb1 mitigates atherosclerosis in part through modulating FTO-mediated m6A RNA modification in NETs-induced endothelial activation - Yang, Zhenni; Xiong, Minqi; Tang, Xinmiao; Wang, Peiwei; Cui, Jingang; Chen, Yu; Zhang, Teng (Frontiers in Pharmacology, 2025)
BackgroundGinsenoside Rb1 (Rb1) exerts pharmacological effects in attenuating the progression of atherosclerosis. However, whether the anti-atherosclerotic effects of Rb1 involve suppressing neutrophil extracellular traps (NETs)-induced endothelial activation and whether N6-methyadenosine (m6A) RNA modification is mechanistically implicated in this process remain unknown.MethodsHigh fat diet (HFD)-fed Apoe−/− mice were subjected to histological, immunohistological and molecular biological analyses. Moreover, NETs-induced endothelial activation and m6A RNA methylation were assessed in human aortic endothelial cells (HAECs).ResultsRb1 mitigated atherosclerotic lesions and endothelial activation in vivo. Rb1 diminished adhesion of neutrophils and monocytes to NETs-stimulated HAECs, offset NETs-upregulated endothelial expression of ICAM1, VCAM1, SELE and SELP, and counteracted NETs-induced endothelial barrier impairment in vitro. NETs exposure significantly decreased the level of m6A RNA methylation and increased the expression of demethylase fat mass and obesity-associated protein (FTO) in HAECs, whereas Rb1 treatment enhanced m6A RNA methylation and reduced FTO expression in the NETs-stimulated HAECs. Overexpression of FTO abrogated the protective effects of Rb1 against NETs-induced endothelial activation in HAECs. Furthermore, Fto overexpression in endothelial cells partially abolished Rb1-confered attenuation of atherosclerotic pathologies and the aortic expression of Vcam1 in HFD-fed Apoe−/− mice.ConclusionThe work here demonstrates that Rb1 mitigates atherosclerosis in part by suppressing NETs-induced endothelial activation. Mechanistically, the pharmacological effects of Rb1 in attenuating NETs-induced endothelial activation are in part mediated by modulating FTO-mediated m6A RNA demethylation in endothelial cells.